Studies on Dynamic Channel Allocation Scheme to Handle Handoff in Wireless Mobile Network - Alagu, S.; Meyyappan, T. (Theory and Practice of Mathematics and Computer Science Vol. 11, 2021)
Because of the significant development in demand for mobile communications, there has been a lot of study into making optimal use of the limited spectrum available for cellular communications. The authors propose a novel call admission control mechanism, DCAS (Dynamic Channel Allocation Scheme), in this work. The number of guard channel(s) is automatically modified in this new method based on the average handoff blocking rate observed over a given period of time. The handoff blocking rate is kept below the set limit, and the new call blocking rate is kept to a minimum. Simulation of nodes is used to evaluate the DCAS's performance. The DCAS method surpasses the Static Channel Allocation Scheme by setting a strict limitation on the likelihood of handoff rejection. The suggested approach provides the best results by optimizing resource consumption and dynamically adapting to changing traffic circumstances.